Mapping stages, barriers and facilitators to the implementation of HEARTS in the Americas initiative in 12 countries: A qualitative study. Issue 4 (18th March 2021) - Giraldo, Gloria P.; Joseph, Kristy T.; Angell, Sonia Y.; Campbell, Norm R. C.; Connell, Kenneth; DiPette, Donald J.; Escobar, Maria C.; Valdés‐Gonzalez, Yamile; Jaffe, Marc G.; Malcolm, Taraleen; Maldonado, Javier; Lopez‐Jaramillo, Patricio; et al.
Abstract: The World Health Organization (WHO) Global Hearts Initiative offers technical packages to reduce the burden of cardiovascular diseases through population‐wide and targeted health services interventions. The Pan American Health Organization (PAHO) has led implementation of the HEARTS in the Americas Initiative since 2016. The authors mapped the developmental stages, barriers, and facilitators to implementation among the 371 primary health care centers in the participating 12 countries. The authors used the qualitative method of document review to examine cumulative country reports, technical meeting notes, and reports to regional stakeholders. Common implementation barriers include segmentation of health systems, overcoming health care professionals' scope of practice legal restrictions, and lack of health information systems limiting operational evaluation and quality improvement mechanisms. Main implementation facilitators include political support from ministries of health and leading scientific societies, PAHO's role as a regional catalyst to implementation, stakeholder endorsement demonstrated by incorporating HEARTS into official documents, and having a health system oriented to primary health care. Key lessons include the need for political commitment and cultivating on‐the‐ground leadership to initiate a shift in hypertension care delivery, accompanied by specific progress in the development of standardized treatment protocols and a set of high‐quality medicines. By systematizing an implementation strategy to ease integration of interventions into delivery processes, the program strengthened technical leadership and ensured sustainability. These study findings will aid the regional approach by providing a staged planning model that incorporates lessons learned. A systematic approach to implementation will enhance equity, efficiency, scale‐up, and sustainability, and ultimately improve population hypertension control.